2013
DOI: 10.5194/nhess-13-1069-2013
|View full text |Cite
|
Sign up to set email alerts
|

Rip current related drowning deaths and rescues in Australia 2004–2011

Abstract: Rip currents are a common hazard to beachgoers found on many beaches around the world, but it has proven difficult to accurately quantify the actual number of rip current related drowning deaths in many regions and countries. Consequently, reported estimates of rip current drowning can fluctuate considerably and are often based on anecdotal evidence. This study aims to quantify the incidence of rip current related drowning deaths and rescues in Australia from 2004 to 2011. A retrospective search was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 18 publications
5
55
2
Order By: Relevance
“…We compare the best available data of annual rip current fatalities (n = 21 yr −1 ; Brighton et al, 2013) in relation to the long-term average of human fatalities caused by the following natural hazards: (1) tropical cyclones; (2) bushfires; (3) floods; and (4) shark attacks. The first three hazards were chosen as they are the most commonly occurring types in Australia (Middelmann, 2007) and are all hydrometeorological by classification.…”
Section: Contextualising the Rip Current Hazardmentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the best available data of annual rip current fatalities (n = 21 yr −1 ; Brighton et al, 2013) in relation to the long-term average of human fatalities caused by the following natural hazards: (1) tropical cyclones; (2) bushfires; (3) floods; and (4) shark attacks. The first three hazards were chosen as they are the most commonly occurring types in Australia (Middelmann, 2007) and are all hydrometeorological by classification.…”
Section: Contextualising the Rip Current Hazardmentioning
confidence: 99%
“…However, these numbers are largely speculative assumptions based on anecdotal information. A recent study by Surf Life Saving Australia, Australia's largest beach safety organisation, using Australia's National Coronial Information System (NCIS) and Media Monitors for the period 1 July 2004 to 20 June 2011 has revealed that the average annual number of confirmed rip current fatalities during this period is 21 yr −1 (Brighton et al, 2013). However, they acknowledged that this number is very likely to be an underestimate as fatalities are only recorded as being rip current related when there is a witness to the event who describes the individual being caught in a rip current.…”
Section: Introductionmentioning
confidence: 99%
“…These strong offshore directed currents are the cause of the majority of fatalities within the beach environment (Drozdzewski et al, 2012;Brander et al, 2013;Brighton et al, 2013;Zhang et al, 2012). Therefore, many attempts have been made to relate the rip current morphology to the local wave climate, shoreline orientation, sediment size and tidal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, rips present a global problem for recreational beach use; in the U.K., 68 % of incidents on beaches patrolled by the Royal National Lifeboat Institution (RNLI) are attributed to rips (Scott et al, 2008). In Australia, rips were a factor in 44 % of recorded beach drownings over a seven-year period (Brighton et al, 2013). Recent research has focussed on assessing the effectiveness of various escape strategies for people caught in rips (Miloshis and Stephenson, 2011;McCarroll et al, 2014aMcCarroll et al, , 2015Castelle et al, 2015;Van Leeuwen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%